Time reconciliation on Fort Marlborough’s design and functions - Serasi, Reko; Hakim, M. Arif Rahman (Ikatan Ahli Arkeologi Malaysia, Universiti Kebangsaan Malaysia, 2019)
Fort Marlborough is one of the tourism objects in Bengkulu. It has withstood for more than 300 years. During its time, it has gone through many things. As a vital asset for Bengkulu province, a special attention is needed in developing and preserving this site. In some cases, there are many historical heritage buildings were gone or in purpose changed. This article tried to discuss Fort Marlborough from time reconciliation point of view. To get better comprehension and understanding about it, an interdisciplinary study is needed. Socio-cultural and historical theories are applied to reach its goals. In conclusion, it was found that Fort Marlborough experienced good and bad time in its life. There were also changes in its design and function. The design was not changed much, but the great changes were found in its functions.